MEMS product development : from concept to commercialization - Fitzgerald, Alissa M.; White, Carolyn D.; Chung, Charles C. (Microsystems and Nanosystems, 2021)
"In this incredibly useful book, the mysteries of MEMS development and manufacturing are spelled out in a clear and thorough and incredibly detailed manner ... I wish I had access to this book during several of my own companies."--Kurt Petersen Drawing on their experiences in successfully executing hundreds of MEMS development projects, the authors present the first practical guide to navigating the technical and business challenges of MEMS product development, from the initial concept stage all the way to commercialization. The strategies and tactics presented, when practiced diligently, can shorten development timelines, help avoid common pitfalls, and improve the odds of success, especially when resources are limited. MEMS Product Development illuminates what it really takes to develop a novel MEMS product so that innovators, designers, entrepreneurs, product managers, investors, and executives may properly prepare their companies to succeed. How to define a MEMS product and create cost models to inform fundraising or budgeting; Implement technical best practices for successful MEMS prototype and product development; Prepare for and successfully execute the transfer of a MEMS prototype to a foundry for volume manufacturing